PENGARUH PENGEMBANGAN KARIR, INSENTIF, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DENGAN KOMITMEN SEBAGAI VARIABEL INTERVENING PADA PT. PEPUTRA MAHA JAYA PEKANBARU - Syahredho Al Idrus; Marnis '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The research was conducted at PT. Peputra Maha Jaya housed in JL.Ahmad Yani / Alamuddinsyah NO. 43 Pekanbaru. The aim of this study was to analyze the effect caused by the variable developing a career, incentives, Work Environment and Work Motivation on Job Satisfaction of employees through commitment .Populasi of this study were all employees of PT. Peputra Maha Jaya with 133 respondents were selected using a sampling saturated. This data retrieval by giving questionnaires to respondents. In terms of data analysis, research using qualitative methods and quantitative methods using SPSS 21.0.Hasil this study indicate career development, incentives, work environment and work motivation having an significant positive toward direct commitment, commitment to career development and significant positive effect on job satisfaction , Incentives, work environment, work motivation is not significant positive effect on job satisfaction. Career development, incentives and motivation of environmental work has a significant positive effect on job satisfaction indirectly through commitment.Keywords: Career Development, incentives, of environmental Work, Work Motivation, Commitment, and Job Satisfaction.